9-Benzyl-6-benzylsulfanyl-9H-purin-2-amine - Hariono, Maywan; Wahab, Habibah A.; Mei, Lan Tan; Rosli, Mohd Mustaqim; Razak, Ibrahim Abdul (International Union of Crystallography, 2014)
In the title compound, C19H17N5S, the dihedral angles between the purine ring system (r.m.s. deviation = 0.009 A°) and the S-bound and methylene-bound phenyl rings are 74.67 (8) and 71.28 (7)°, respectively. In the crystal, inversion dimers linked by pairs of N—H...N hydrogen bonds generate R2/2(8) loops. C—H...N interactions link the dimers into (100) sheets.